Empowering Principals for Lifelong Learning: Self-directed Approaches in Digitalized Information Systems - Yuan Zhou; Piyapong Sumettikoon (My University, 2024)
The study delves into the dynamic interplay between digitalized information systems, competencies, self-directed learning, and lifelong learning in the context of the contemporary educational landscape. With the integration of Artificial Intelligence (AI) and evolving competencies becoming integral to education, understanding their combined impact on individuals' attitudes toward lifelong learning is paramount. Past research has explored these elements individually, but a comprehensive examination of their interconnected relationships remains scarce. The primary purpose is to investigate how AI integration, competencies, and self-directed learning collectively influence lifelong learning attitudes. The study aims to uncover the intricate dynamics by exploring the impact of digitalized information systems on competencies, the mediating role of self-directed learning, and the overall implications for lifelong learning behaviors. Utilizing a quantitative approach, the study focuses on teachers in China, distributing 500 questionnaires and receiving 340 responses. The research design incorporates a cross-sectional survey methodology, employing a structured questionnaire to gather data on AI integration, competencies, self-directed learning, and lifelong learning attitudes. Preliminary findings reveal significant correlations between AI integration, competencies, self-directed learning, and lifelong learning attitudes. The study observes the mediating role of self-directed learning, highlighting its importance in shaping the relationship between digitalized information systems, competencies, and the inclination toward lifelong learning. This research contributes to the theoretical understanding of the complex relationships in contemporary education. Its originality lies in integrating AI integration, competencies, and self-directed learning into a comprehensive framework.
Keywords: Autodidacticism; Digital literacy in education